Preparation method of wood-based carbon material for improving performance of supercapacitor
Through a simple and efficient processing strategy, the preparation of wood-based graded porous carbon materials is solved by using barshamu and high-concentration zinc chloride solutions, and the problems of existing process complexity and raw material instability are achieved, and electrode preparation with high specific surface area and good pore structure is significantly improved, which significantly improves the performance of supercapacitors.
Patent Information
- Application Number
- CN202411751276.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The existing biomass carbon material preparation process has raw material scarcity and instability, and requires multiple process steps, which increases the complexity and time cost of preparation, making it difficult to meet the needs of improving the performance of supercapacitors.
A simple, gentle and efficient processing strategy is adopted to prepare wood-based graded porous carbon materials by cutting barsalwood into thin wood slices, sonication and delignification, followed by high-concentration zinc chloride solution to dissolve cellulose and regeneration, and finally, through high-temperature carbonization and washing steps.
This method not only saves time and cost, improves safety and efficiency, but also successfully prepares wood-based porous carbon electrodes with high specific surface area and good pore structure by improving the surface morphology and pore structure of the wood, which significantly improves the electrochemical performance of the supercapacitor.
Smart Images

Figure CN119581241A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of improving supercapacitor performance, and in particular to a method for preparing a wood-based carbon material for improving supercapacitor performance. Background Art
[0002] With the rapid advancement and continuous expansion of the global economy, the consumption of energy resources is rising at an unprecedented rate. At the same time, the maturity of renewable and environmentally friendly energy systems such as hydrogen energy and wind energy has accelerated the vigorous development of the energy storage industry. Supercapacitors, with their fast charging and discharging speed, long service life and excellent power density, balance the output power by effectively recovering intermittent energy, thereby ensuring the storage efficiency and stability of the entire energy storage power supply system. Supercapacitor electrode materials prepared from biomass carbon materials have the advantages of high specific capacity, large power density, wide operating temperature range and long cycle life, and have broad application prospects in electric vehicles, energy storage systems, chemical electronic devices and other fields. As a highly renewable natural porous matrix, wood contains rich and diverse functional group structures and unique vertical microchannel networks. These characteristics provide extremely favorable conditions for the rapid transmission and efficient accumulation of charges in the material. In order to further improve the electrochemical performance of wood-based carbon electrodes, researchers have developed a variety of efficient modification methods, such as surface functionalization, heteroatom doping and deposition of pseudocapacitive materials to further design and optimize the wood structure. In the preparation of porous carbon materials, the commonly used methods include template method and activation method, which control the pore structure and morphology of carbon materials by introducing templates and activators. These methods can prepare porous carbon materials with rich pore structure and good conductivity, which are suitable for the preparation of electrodes for high-performance supercapacitors. Although previous studies have demonstrated the great potential of biomass carbon materials as electrodes in supercapacitors, so far, further optimization of the preparation process is needed to accurately control the size, shape and distribution of pores, improve the bonding force between materials and improve electrochemical performance.
[0003] Patent publication number CN 116936264 A discloses a biomass-based nitrogen-doped graded porous carbon material and its preparation and application. In the patent publication, Houttuynia cordata, a dopant and an activator are uniformly stirred mechanically, activated at high temperature, washed and dried to obtain biomass-based nitrogen-doped graded porous carbon for supercapacitors. The disadvantages are the scarcity and instability of the raw materials, and multiple process steps are required, which increases the complexity and time cost of the preparation. Patent publication number CN 116002661 A discloses a phosphorus-doped microbial modified biomass carbon material, a preparation method and application. In the patent publication, microorganisms are cultured on biomass materials to obtain microbial modified biomass materials, and further phosphorus source solution impregnation and carbonization treatment are performed to obtain phosphorus-doped microbial modified biomass carbon materials. The disadvantage is that the screening of microorganisms has a great influence on the performance of the final product, and the production efficiency of phosphorus-doped microbial modified biomass carbon materials may be low, which requires a lot of time and effort for research and optimization.
[0004] It can be seen that the existing materials and methods cannot fully meet the use requirements. Therefore, the present invention provides a simple, mild and efficient processing strategy to prepare wood-based hierarchical porous carbon materials, which not only saves time and cost, improves safety and efficiency, but also grows spherical flower clusters in the wood structure through dissolution-regeneration treatment with high-concentration zinc chloride solution, thereby effectively improving the surface morphology of the wood and obtaining a more uniform hierarchical porous structure; thereby successfully preparing a wood-based porous carbon electrode with a high specific surface area and a good pore structure and applying it to supercapacitors. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing a wood-based carbon material for improving the performance of a supercapacitor.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A method for preparing a wood-based carbon material for improving the performance of a supercapacitor comprises the following steps:
[0008] Step 1: cutting balsa wood into thin wood chips, immersing the wood chips in anhydrous ethanol, ultrasonically treating, and drying to obtain natural wood chip samples;
[0009] Step 2: Remove lignin from natural wood chips using a NaClO2 / CH3COOH solvent system, wash the chips with deionized water for multiple times until the pH is neutral, and freeze-dry the sample to obtain delignified wood chips;
[0010] Step 3: Dissolve cellulose with a highly concentrated zinc chloride solution, and use deionized water as a coagulation bath to precipitate regenerated cellulose. Then, freeze-dry the regenerated delignified wood chips to obtain a wood sample RC@ZnODWx with regenerated cellulose and ZnO growing on the surface.
[0011] Step 4: The obtained regenerated cellulose wood chips RC@ZnODW were placed in a tube furnace, heated in a N2 atmosphere, and cooled to room temperature to obtain a wood-based hierarchical porous carbon product, which was then washed in an HF / HCl solution and washed with deionized water until neutral, and dried to obtain a carbon sample named CRCDWx, and the carbonized product was then cut;
[0012] Step 5: The obtained wood-based hierarchical porous carbon CRCDW electrode is used as the positive electrode, zinc foil as the negative electrode, and the organic gel as the electrolyte and separator, and a metal shell is used to prepare a CRCDW-based zinc ion hybrid supercapacitor CRCDW / / Zn;
[0013] Conduct electrochemical performance tests on supercapacitor CRCDW / / Zn and analyze its capacitance characteristics;
[0014] Three techniques are generally used to characterize the capacitive behavior of supercapacitors: cyclic voltammetry (CV), constant current charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS);
[0015] These methods generally measure three basic parameters, namely current, voltage and time, from which important parameter indicators for evaluating the energy density and power density of electrode materials, such as capacitance, voltage window and interface impedance, can be derived.
[0016] Preferably, in step 1, the balsa wood is cut into pieces with a size of 2.0×2.0 cm 2 The balsa wood chips are immersed in anhydrous ethanol for 1 min to 90 min under ultrasonication, and dried in an oven for 2 h to 30 h at a temperature of 50°C to 90°C.
[0017] Preferably, in step 2, the method for removing lignin from natural wood chips by using the NaClO2 / CH3COOH solvent system is:
[0018] The prepared sodium chlorite aqueous solution and acetic acid buffer solution are adjusted to a pH value of 4.6, and then the wood chip sample is placed in an acidic sodium chlorite solution and treated at 20°C to 100°C for 2h to 12h for delignification; after the delignification is completed, the wood chips turn white, indicating that the lignin is successfully removed.
[0019] Preferably, the mass fraction of the prepared sodium chlorite aqueous solution is 1wt% to 10wt%, and the mass fraction of the acetic acid buffer solution is 1wt% to 10wt%.
[0020] Preferably, in step 3, the method for precipitating the regenerated cellulose is:
[0021] First, the dried delignified wood chips are immersed in a zinc chloride solution at room temperature until they are completely penetrated by the salt solution; then, the highly concentrated zinc chloride solution containing the delignified wood chips is heated in a water bath at high temperature for 0.1h to 30h to dissolve part of the cellulose on the wood chips; after the heating is completed, the whole is taken out and cooled at room temperature for 10min to 120min, and then the partially dissolved delignified wood chips are transferred to deionized water and immersed for 10h to 60h for cellulose regeneration.
[0022] Preferably, the dried delignified wood chips are immersed in a 30wt% to 80wt% zinc chloride solution at room temperature for a soaking time of 10min to 100min.
[0023] Preferably, the highly concentrated zinc chloride solution containing delignified wood chips is heated in a water bath at 40° C. to 90° C. to continuously dissolve part of the cellulose on the wood chips.
[0024] Preferably, in step 4, the obtained regenerated cellulose wood chips are placed in a tube furnace, heated to 800° C. at a rate of 1 to 5° C. / min in a N 2 atmosphere and maintained for 60 to 400 min.
[0025] Preferably, in step 4, after obtaining the wood-based hierarchical porous carbon product, it is washed in HF / HCl solution for 5 min to 60 min to completely remove transition metal impurities in the sample.
[0026] Preferably, in step 4, the drying time is 24 hours and the drying temperature is 60°C; the carbonized product is cut so that the working area of the wood carbon electrode is fixed at 1.0×1.0 cm 2 .
[0027] Compared with the prior art, the present invention has achieved the following technical effects:
[0028] (1) The wood-based material used in the method of the present invention is low-cost and renewable, which reduces the dependence on traditional electrode materials and reduces environmental pollution; and the wood-based material has a natural porous structure, in which the pores are vertically arranged, the channels are straight, and the pore structure is uniform, which is very suitable for constructing thick electrochemical supercapacitor electrodes with high energy density. By adjusting the pore structure of the wood-based material, the capacitance performance of the electrode can be optimized;
[0029] (2) The method of the present invention prepares delignified wood chips by delignifying natural wood chips; this operation removes most of the lignin and hemicellulose from the wood cell walls, while the wood as a whole can still maintain the integrity of the macro and micro structures, and introduces more nanopores on the cell walls, greatly increasing the porosity, which helps to improve the specific surface area of the carbon material, thereby improving the electrochemical performance of the carbon material;
[0030] (3) The high concentration zinc chloride solution treatment in the method of the present invention has a significant effect on the morphology of wood-based porous carbon; zinc chloride is not only a solvent for cellulose, which can dissolve part of the cellulose on the surface of the wood chips to modify the wood chips, but also acts as a Zn 2+ The precursor is used to synthesize ZnO nanoparticles in the wood chip structure. Meanwhile, regenerated cellulose is used as an organic carbon source to grow in situ with ZnO nanoparticles to form a composite nanosheet (RCellulose@ZnO) structure with the surface coated with regenerated cellulose. The composite nanosheets are self-assembled to obtain a flower-like structure formed by interweaving sheets.
[0031] (4) The flower-like wood-based hierarchical porous carbon prepared by the chemical dissolution-regeneration method of the present invention has good surface wettability, which can enhance the accessibility of ions and is beneficial to improving the electrochemical performance of the carbon electrode;
[0032] (5) In the method of the present invention, a wood-based hierarchical porous carbon electrode CRCDW2 is used as the positive electrode, zinc foil is used as the negative electrode, and organic gel is selected as the electrolyte and separator to construct an all-solid-state wood-based zinc ion hybrid supercapacitor (CRCDW2 / / Zn), which provides a simple and effective innovative strategy for the successful manufacture of wood-based hierarchical porous carbon electrodes, thereby improving the performance of supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope (SEM) image of wood carbon (CNW) obtained by high-temperature carbonization of natural wood chips without delignification in Comparative Example 1 of the present invention;
[0034] Figure 2 This is a scanning electron microscope (SEM) image of wood carbon (CDW) obtained after high-temperature carbonization of wood chips after delignification in Comparative Example 2 of the present invention;
[0035] Figure 3 This is a scanning electron microscope (SEM) image of a wood-based porous material obtained by treating delignified wood chips with a high concentration ZnCl2 solution and then carbonizing them at high temperature after reacting for 2 hours in Example 1 of the present invention;
[0036] Figure 4This is a scanning electron microscope (SEM) image of a wood-based porous material obtained by treating delignified wood chips with a high concentration ZnCl2 solution and then carbonizing them at high temperature after reacting for 1 hour in Example 2 of the present invention;
[0037] Figure 5 This is a scanning electron microscope (SEM) image of a wood-based porous material obtained by treating delignified wood chips with a high concentration ZnCl2 solution and reacting for 2.5 hours and then carbonizing at high temperature in Example 3 of the present invention;
[0038] Figure 6 CV curves of different wood-based carbon electrode samples at a scan rate of 10 mV / s in the method of the present invention;
[0039] Figure 7 : GCD curves of different wood-based carbon electrode samples at a current density of 1 A / g in the method of the present invention;
[0040] Figure 8 : EIS curves of different wood-based carbon electrode samples in the method of the present invention. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The present invention discloses a method for preparing a wood-based carbon material for improving the performance of a supercapacitor, comprising the following steps:
[0043] Step 1: Cut the balsa wood into pieces with a size of 2.0 x 2.0 cm 2 A square wood chip with a thickness of 1 mm is immersed in anhydrous ethanol, subjected to ultrasonic treatment for 1 min to 90 min, and dried in an oven at 50° C. to 90° C. for 2 h to 30 h to obtain a natural wood chip sample;
[0044] Step 2: removing lignin from natural wood chips by a NaClO2 / CH3COOH solvent system, wherein the removal method is as follows: adjusting the pH value of a prepared sodium chlorite aqueous solution and an acetic acid buffer solution to 4.6, and then placing the wood chip sample in an acidic sodium chlorite solution and treating it at 20°C to 100°C for 2h to 12h for delignification; after the delignification is completed, the wood chips turn white, indicating that the lignin is successfully removed; the mass fraction of the prepared sodium chlorite aqueous solution is 1wt% to 10wt%, and the mass fraction of the acetic acid buffer solution is 1wt% to 10wt%; and washing the wood chips with deionized water for multiple times until the pH is neutral, and freeze-drying the sample to obtain delignified wood chips;
[0045] Step 3: Dissolve cellulose with a high-concentration zinc chloride solution, and use deionized water as a coagulation bath to precipitate regenerated cellulose. The precipitation method is as follows: first, immerse the dried delignified wood chips in a zinc chloride solution at room temperature until they are completely penetrated by the salt solution; then, heat the high-concentration zinc chloride solution containing delignified wood chips at high temperature for 0.1h to 30h in a water bath to dissolve part of the cellulose on the wood chips; after the heating is completed, take it out as a whole and cool it at room temperature for 10min to 120min, and then transfer the partially dissolved delignified wood chips to a The method comprises the following steps: transferring the dried delignified wood chips to deionized water and soaking them for 10 to 60 hours to regenerate cellulose; immersing the dried delignified wood chips in a 30 wt% to 80 wt% zinc chloride solution at room temperature for 10 to 100 minutes; heating the delignified wood chips by a water bath to continuously dissolve part of the cellulose on the wood chips at 40 to 90 degrees Celsius; and then drying the regenerated delignified wood chips by freeze drying to obtain a wood sample RC@ZnODWx with regenerated cellulose and ZnO grown on the surface;
[0046] Step 4: The obtained regenerated cellulose wood chips RC@ZnODW were placed in a tube furnace, heated to 800°C at a rate of 1-5°C / min in a N2 atmosphere and maintained for 60min-400min, and cooled to room temperature to obtain a wood-based hierarchical porous carbon product. The product was then washed in HF / HCl solution for 5min-60min to completely remove transition metal impurities in the sample, washed with deionized water to neutrality, and dried at 60°C for 24h to obtain a carbon sample named CRCDWx. The carbonized product was then trimmed so that the working area of the wood carbon electrode was fixed at 1.0×1.0cm 2 ;
[0047] Step 5: The obtained wood-based hierarchical porous carbon CRCDW electrode is used as the positive electrode, zinc foil as the negative electrode, and the organic gel as the electrolyte and separator, and a metal shell is used to prepare a CRCDW-based zinc ion hybrid supercapacitor CRCDW / / Zn;
[0048] The electrochemical performance of the supercapacitor CRCDW / / Zn was tested to analyze its capacitance characteristics. Three techniques are generally used to characterize the capacitance behavior of supercapacitors: cyclic voltammetry (CV), constant current charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS);
[0049] These methods generally measure three basic parameters, namely current, voltage and time, from which important parameter indicators for evaluating the energy density and power density of electrode materials, such as capacitance, voltage window and interface impedance, can be derived.
[0050] Experimental Example 1:
[0051] A method for preparing a wood-based carbon material for improving the performance of a supercapacitor comprises the following steps:
[0052] (1) Cut the balsa wood parallel to the tree growth direction into pieces of 2.0 x 2.0 cm 2 Square thin wood chips with a thickness of about 1 mm were prepared. Then, the wood chips were immersed in anhydrous ethanol and ultrasonically treated to remove impurities, and natural wood chip (NW) samples were obtained after drying in a vacuum oven at 80°C. The lignin in NW was removed by a NaClO2 / CH3COOH solvent system: the prepared sodium chlorite (NaClO2) aqueous solution and acetic acid buffer solution were adjusted to a pH value of 4.6, and then the wood chip sample (NW) was placed in an acidic NaClO2 solution and treated at 80°C for 6h for delignification. After delignification, the wood chips turned white, indicating that the lignin was successfully removed, and the wood chips were washed with deionized water multiple times to further remove residual metal salts and solvents until the pH was neutral. Finally, the sample was freeze-dried to obtain delignified wood chips (DW) for future use.
[0053] (2) Dissolving cellulose with a highly concentrated zinc chloride (ZnCl2) solution and using deionized water as a coagulation bath to precipitate regenerated cellulose:
[0054] ZnCl2 solution concentration: 75wt%;
[0055] The high-concentration ZnCl2 solution containing DW was heated in a water bath to maintain high temperature for 2 h;
[0056] First, the dried DW was immersed in a ZnCl2 solution at room temperature until it was completely penetrated by the salt solution. Subsequently, the high-concentration ZnCl2 solution containing DW was heated in a water bath for 2 hours at high temperature to dissolve part of the cellulose on the wood chips. After the heating was completed, it was taken out as a whole and cooled at room temperature for 30 minutes. The partially dissolved DW was then transferred to deionized water and immersed for 36 hours for cellulose regeneration. Finally, the regenerated DW was dried by freeze drying to obtain the wood sample RC@ZnODW with regenerated cellulose and ZnO growing on the surface. x .
[0057] (3) The obtained regenerated cellulose wood chips (RC@ZnODW) were placed in a tube furnace, heated to a certain temperature in a N2 atmosphere, and waited for self-cooling to room temperature 25°C to obtain a wood-based hierarchical porous carbon product, and then washed in HF / HCl solution to completely remove transition metal impurities in the sample. After that, it was washed with deionized water several times until neutral, and dried at 60°C for 24h. The final carbon sample was named CRCDW. x , the sample was prepared for scanning electron microscopy (SEM). The test results are shown in Figure 3 .
[0058] (4) The obtained wood-based hierarchical porous carbon (CRCDW) electrode was used as the positive electrode, zinc foil as the negative electrode, organic gel as the electrolyte and separator, and the corresponding metal shell was used to prepare a CRCDW-based zinc ion hybrid supercapacitor (CRCDW / / Zn).
[0059] (5) The electrochemical performance of the supercapacitor CRCDW / / Zn was tested to analyze its capacitance characteristics. Three techniques are generally used to characterize the capacitance behavior of supercapacitors: cyclic voltammetry (CV), constant current charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS).
[0060] Experimental Example 2:
[0061] A method for preparing a wood-based carbon material for improving the performance of a supercapacitor comprises the following steps:
[0062] (1) Cut the balsa wood parallel to the tree growth direction into pieces of 2.0 x 2.0 cm 2 Square thin wood chips with a thickness of about 1 mm were prepared. Then, the wood chips were immersed in anhydrous ethanol and ultrasonically treated to remove impurities, and natural wood chip (NW) samples were obtained after drying in a vacuum oven at 80°C. The lignin in NW was removed by a NaClO2 / CH3COOH solvent system: the prepared sodium chlorite (NaClO2) aqueous solution and acetic acid buffer solution were adjusted to a pH value of 4.6, and then the wood chip sample (NW) was placed in an acidic NaClO2 solution and treated at 80°C for 6h for delignification. After delignification, the wood chips turned white, indicating that the lignin was successfully removed, and the wood chips were washed with deionized water multiple times to further remove residual metal salts and solvents until the pH was neutral. Finally, the sample was freeze-dried to obtain delignified wood chips (DW) for future use.
[0063] (2) Dissolving cellulose with a highly concentrated zinc chloride (ZnCl2) solution and using deionized water as a coagulation bath to precipitate regenerated cellulose:
[0064] ZnCl2 solution concentration: 75wt%;
[0065] The high-concentration ZnCl2 solution containing DW was heated in a water bath to maintain high temperature for 1 h;
[0066] First, the dried DW was immersed in a ZnCl2 solution at room temperature until it was completely penetrated by the salt solution. Subsequently, the high-concentration ZnCl2 solution containing DW was heated in a water bath at high temperature for 1 hour to dissolve part of the cellulose on the wood chips. After the heating was completed, it was taken out as a whole and cooled at room temperature for 30 minutes. The partially dissolved DW was then transferred to deionized water and immersed in 36 hours for cellulose regeneration. Finally, the regenerated DW was dried by freeze drying to obtain the wood sample RC@ZnODW with regenerated cellulose and ZnO growing on the surface. x .
[0067] (3) The obtained regenerated cellulose wood chips (RC@ZnODW) were placed in a tube furnace, heated to a certain temperature in a N2 atmosphere, and waited for self-cooling to room temperature 25°C to obtain a wood-based hierarchical porous carbon product, and then washed in HF / HCl solution to completely remove transition metal impurities in the sample. After that, it was washed with deionized water several times until neutral, and dried at 60°C for 24h. The final carbon sample was named CRCDW. x , the sample was prepared for scanning electron microscopy (SEM). The test results are shown in Figure 4 .
[0068] (4) The obtained wood-based hierarchical porous carbon (CRCDW) electrode was used as the positive electrode, zinc foil as the negative electrode, organic gel as the electrolyte and separator, and the corresponding metal shell was used to prepare a CRCDW-based zinc ion hybrid supercapacitor (CRCDW / / Zn).
[0069] (5) The electrochemical performance of the supercapacitor CRCDW / / Zn was tested to analyze its capacitance characteristics. Three techniques are generally used to characterize the capacitance behavior of supercapacitors: cyclic voltammetry (CV), constant current charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS).
[0070] Experimental Example 3
[0071] A method for preparing a wood-based carbon material for improving the performance of a supercapacitor comprises the following steps:
[0072] (1) Cut the balsa wood parallel to the tree growth direction into pieces of 2.0 x 2.0 cm 2Square thin wood chips with a thickness of about 1 mm were prepared. Then, the wood chips were immersed in anhydrous ethanol and ultrasonically treated to remove impurities, and natural wood chip (NW) samples were obtained after drying in a vacuum oven at 80°C. The lignin in NW was removed by a NaClO2 / CH3COOH solvent system: the prepared sodium chlorite (NaClO2) aqueous solution and acetic acid buffer solution were adjusted to a pH value of 4.6, and then the wood chip sample (NW) was placed in an acidic NaClO2 solution and treated at 80°C for 6h for delignification. After delignification, the wood chips turned white, indicating that the lignin was successfully removed, and the wood chips were washed with deionized water multiple times to further remove residual metal salts and solvents until the pH was neutral. Finally, the sample was freeze-dried to obtain delignified wood chips (DW) for future use.
[0073] (2) Dissolving cellulose with a highly concentrated zinc chloride (ZnCl2) solution and using deionized water as a coagulation bath to precipitate regenerated cellulose:
[0074] ZnCl2 solution concentration: 75wt%;
[0075] The high-concentration ZnCl2 solution containing DW was heated in a water bath to maintain high temperature for 2.5 h;
[0076] First, the dried DW was immersed in a ZnCl2 solution at room temperature until it was completely penetrated by the salt solution. Subsequently, the high-concentration ZnCl2 solution containing DW was heated in a water bath at high temperature for 2.5 hours to dissolve part of the cellulose on the wood chips. After the heating was completed, it was taken out as a whole and cooled at room temperature for 30 minutes. The partially dissolved DW was then transferred to deionized water and immersed for 36 hours for cellulose regeneration. Finally, the regenerated DW was dried by freeze drying to obtain the wood sample RC@ZnODW with regenerated cellulose and ZnO growing on the surface. x .
[0077] (3) The obtained regenerated cellulose wood chips (RC@ZnODW) were placed in a tube furnace, heated to a certain temperature in a N2 atmosphere, and waited for self-cooling to room temperature 25°C to obtain a wood-based hierarchical porous carbon product, and then washed in HF / HCl solution to completely remove transition metal impurities in the sample. After that, it was washed with deionized water several times until neutral, and dried at 60°C for 24h. The carbon sample finally obtained was named CRCDWx, and the sample was prepared for scanning electron microscopy (SEM) testing. The test results are shown in Figure 5 .
[0078] (4) The obtained wood-based hierarchical porous carbon (CRCDW) electrode was used as the positive electrode, zinc foil as the negative electrode, organic gel as the electrolyte and separator, and the corresponding metal shell was used to prepare a CRCDW-based zinc ion hybrid supercapacitor (CRCDW / / Zn).
[0079] (5) The electrochemical performance of the supercapacitor CRCDW / / Zn was tested to analyze its capacitance characteristics. Three techniques are generally used to characterize the capacitance behavior of supercapacitors: cyclic voltammetry (CV), constant current charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS).
[0080] Comparative Example 1
[0081] The following steps are involved:
[0082] (1) Cut the balsa wood parallel to the tree growth direction into pieces of 2.0 x 2.0 cm 2 The square wood chips were about 1 mm thick. Then, the wood chips were immersed in anhydrous ethanol and ultrasonicated to remove impurities, and dried in a vacuum oven at 80 °C to obtain natural wood chip (NW) samples.
[0083] (2) Place natural wood chips (NW) in a tube furnace, heat to a certain temperature in a N2 atmosphere, and wait for them to cool down to room temperature 25°C to obtain a wood-based hierarchical porous carbon product, then wash it in HF / HCl solution to completely remove transition metal impurities in the sample. After that, wash it with deionized water several times until it is neutral, and dry it at 60°C for 24h. The carbon sample finally obtained is named CNW, and the sample is prepared for scanning electron microscopy (SEM) testing. The test results are shown in Figure 1
[0084] (3) The obtained wood-based hierarchical porous carbon (CNW) electrode was used as the positive electrode, zinc foil as the negative electrode, organic gel as the electrolyte and separator, and the corresponding metal shell was used to prepare CRCDW-based zinc ion hybrid supercapacitors (CRCDW / / Zn).
[0085] (4) The electrochemical performance of the supercapacitor CRCDW / / Zn was tested to analyze its capacitance characteristics. Three techniques are generally used to characterize the capacitance behavior of supercapacitors: cyclic voltammetry (CV), constant current charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS).
[0086] Comparative Example 2:
[0087] The following steps are involved:
[0088] (1) Cut the balsa wood parallel to the tree growth direction into pieces of 2.0 x 2.0 cm 2 The square wood chips were about 1 mm thick. Then, the wood chips were immersed in anhydrous ethanol and ultrasonicated to remove impurities, and dried in a vacuum oven at 80 °C to obtain natural wood chip (NW) samples.
[0089] Lignin in NW was removed by NaClO2 / CH3COOH solvent system: the pH value of the prepared sodium chlorite (NaClO2) aqueous solution and acetic acid buffer solution was adjusted to 4.6, and then the wood chip sample (NW) was placed in an acidic NaClO2 solution and treated at 80°C for 6h for delignification. After delignification, the wood chips turned white, indicating that the lignin was successfully removed, and the wood chips were washed with deionized water several times to further remove residual metal salts and solvents until the pH was neutral. Finally, the sample was freeze-dried to obtain delignified wood chips (DW) for future use.
[0090] (2) The delignified wood chips (DW) were placed in a tube furnace, heated to a certain temperature in a N2 atmosphere, and waited for self-cooling to room temperature 25°C to obtain a wood-based hierarchical porous carbon product, which was then washed in an HF / HCl solution to completely remove transition metal impurities in the sample. Afterwards, it was washed multiple times with deionized water until neutral and dried at 60°C for 24 hours. The carbon sample finally obtained was named CDW and prepared for scanning electron microscopy (SEM) testing. The test results are shown in Figure 2 .
[0091] (3) The obtained wood-based hierarchical porous carbon (CNW) electrode was used as the positive electrode, zinc foil as the negative electrode, organic gel as the electrolyte and separator, and the corresponding metal shell was used to prepare CRCDW-based zinc ion hybrid supercapacitors (CRCDW / / Zn).
[0092] (4) The electrochemical performance of the supercapacitor CRCDW / / Zn was tested to analyze its capacitance characteristics. Three techniques are generally used to characterize the capacitance behavior of supercapacitors: cyclic voltammetry (CV), constant current charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS).
[0093] It can be seen from Comparative Examples 1 and 2 that the natural wood chips (NW) have a light yellow appearance, a dense cell wall layer on the surface, and are smooth and wrinkle-free. Since the one-way channels in the wood structure can provide sufficient mechanical strength, after high-temperature carbonization, the wood carbon (CNW) can still retain these richly arranged channels to support the construction of the excellent pore structure of the electrode. At the same time, this also reduces the transmission resistance of ions to ensure the accelerated transmission of ions in the channel, thereby giving the wood carbon electrode high conductivity.
[0094] In Comparative Example 2, when most of the lignin and hemicellulose are removed from the wood cell wall, the wood as a whole can still maintain the integrity of the macroscopic and microscopic structure. And more nanopores will be introduced into the cell wall, greatly increasing the porosity. Delignified wood carbon (CDW) still has these natural pore structures, which helps to improve the specific surface area of the carbon material. These pit structures on the channel wall not only promote the interconnection between adjacent channels, but also can serve as a buffer chamber for electrolyte ions in supercapacitors, which is conducive to the rapid penetration and transfer of electrolytes and improves the electrochemical performance of carbon materials.
[0095] It can be seen from Comparative Example 1 and Example 1 that the electrode obtained by direct carbonization of natural wood chips has only a weak specific capacitance. As delignification and ZnCl2 solution treatment proceed, the wood-based carbon material obtains a flaky cluster structure with a high specific surface area, and the specific capacitance gradually increases.
[0096] It can be seen from Examples 1 and 2 that in the process of treating delignified wood chips with high-concentration ZnCl2 solution, the ZnCl2 solution has a dual role: it is not only a solvent for cellulose, which can dissolve part of the cellulose on the surface of the wood chips to modify the wood chips, but also acts as a Zn 2+ The precursor is used to synthesize ZnO nanoparticles in the wood chip structure, and finally in situ growth is performed to form a composite nanosheet structure with regenerated cellulose coated on the surface. After 1 hour of treatment, these RCellulose@ZnO nanosheets on the surface of the recycled wood chip RC@ZnODW1 gradually began to self-assemble together to form a flaky flower structure, and after 2 hours, the three-dimensional spherical flower structure on the surface of the recycled wood chip can be clearly seen. A series of carbonized delignified wood chips of regenerated cellulose (CRCDW), the nanosheets on the surface and the self-assembled flaky flower structure can still be well preserved.
[0097] It can be seen from Example 1 and Example 3 that when the ZnCl2 solution treatment time is too long, the treatment is continued for 2.5 hours, RC@ZnODW 2.5 The spherical flowers on the surface will become more dense, the diameter will also decrease, and the secondary growth of nanosheets will appear on the flower cluster structure. Part of the surface of the flake flowers will be covered by the newly grown nanosheets, resulting in the carbonization of the wood chips CRCDW 2.5 The flower cluster structure on the surface collapsed, which ultimately led to a decrease in the specific surface area and specific capacitance of the carbon material.
[0098] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a wood-based carbon material for improving the performance of a supercapacitor, characterized in that: The following steps are involved: Step 1: cutting balsa wood into thin wood chips, immersing the wood chips in anhydrous ethanol, ultrasonically treating, and drying to obtain natural wood chip samples; Step 2: Remove lignin from natural wood chips using a NaClO2 / CH3COOH solvent system, wash the chips with deionized water for multiple times until the pH is neutral, and freeze-dry the sample to obtain delignified wood chips; Step 3: Dissolve cellulose with a highly concentrated zinc chloride solution, and use deionized water as a coagulation bath to precipitate regenerated cellulose. Then, freeze-dry the regenerated delignified wood chips to obtain a wood sample RC@ZnODWx with regenerated cellulose and ZnO growing on the surface. Step 4: The obtained regenerated cellulose wood chips RC@ZnODW were placed in a tube furnace, heated in a N2 atmosphere, and cooled to room temperature to obtain a wood-based hierarchical porous carbon product, which was then washed in an HF / HCl solution and washed with deionized water until neutral, and dried to obtain a carbon sample named CRCDWx, and the carbonized product was then cut; Step 5: The obtained wood-based hierarchical porous carbon CRCDW electrode is used as the positive electrode, zinc foil as the negative electrode, and the organic gel as the electrolyte and separator, and a metal shell is used to prepare a CRCDW-based zinc ion hybrid supercapacitor CRCDW / / Zn. The electrochemical performance of the supercapacitor is tested to analyze its capacitance characteristics.
2. A method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 1, characterized in that: In step 1, the balsa wood is cut into pieces with a size of 2.0×2.0 cm. 2 The balsa wood chips are immersed in anhydrous ethanol and ultrasonically treated for 1 min to 90 min, and dried in an oven for 2 h to 30 h at a temperature of 50°C to 90°C.
3. The method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 1, characterized in that: In step 2, the method for removing lignin from natural wood chips by using the NaClO2 / CH3COOH solvent system is: The prepared sodium chlorite aqueous solution and acetic acid buffer solution are adjusted to a pH value of 4.6, and then the wood chip sample is placed in an acidic sodium chlorite solution and treated at 20°C to 100°C for 2h to 12h for delignification; after the delignification is completed, the wood chips turn white, indicating that the lignin is successfully removed.
4. The method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 3, characterized in that: The mass fraction of the prepared sodium chlorite aqueous solution is 1wt% to 10wt%, and the mass fraction of the acetic acid buffer solution is 1wt% to 10wt%.
5. The method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 1, characterized in that: In step 3, the method for precipitating regenerated cellulose is as follows: First, the dried delignified wood chips are immersed in a zinc chloride solution at room temperature until they are completely penetrated by the salt solution; then, the highly concentrated zinc chloride solution containing the delignified wood chips is heated in a water bath at high temperature for 0.1h to 30h to dissolve part of the cellulose on the wood chips; After the heating is completed, the whole wood chip is taken out and cooled at room temperature for 10 to 120 minutes, and then the partially dissolved delignified wood chips are transferred to deionized water and soaked for 10 to 60 hours for cellulose regeneration.
6. A method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 5, characterized in that: The dried delignified wood chips are immersed in a 30wt% to 80wt% zinc chloride solution at room temperature for 10min to 100min.
7. The method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 5, characterized in that: The water bath heating is used to continuously dissolve part of the cellulose on the wood chips at a temperature of 40° C. to 90° C. using a highly concentrated zinc chloride solution containing delignified wood chips.
8. The method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 1, characterized in that: In the step 4, the obtained regenerated cellulose wood chips are placed in a tube furnace, heated to 800° C. at a rate of 1 to 5° C. / min in a N2 atmosphere and maintained for 60 to 400 minutes.
9. The method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 1, characterized in that: In the step 4, after obtaining the wood-based hierarchical porous carbon product, it is washed in a HF / HCl solution for 5 minutes to 60 minutes to completely remove transition metal impurities in the sample.
10. The method for preparing a wood-based carbon material for improving supercapacitor performance according to claim 1, characterized in that: In step 4, the drying time is 24 hours and the drying temperature is 60° C. The carbonized product is cut so that the working area of the wood carbon electrode is fixed at 1.0×1.0 cm 2 .
Citation Information
Patent Citations
Phosphorus-doped microorganism modified biomass carbon material, preparation method and application
CN116002661A
Biomass-based nitrogen-doped graded porous carbon material as well as preparation and application thereof
CN116936264A
Cited By
Bio-based flexible pressure-sensitive conductive material prepared by low-temperature carbonization method
CN120622458A
Co-Zn / wood source porous activated carbon composite material, preparation method, application and supercapacitor comprising Co-Zn / wood source porous activated carbon composite material
CN121768863A